Analysis Performance of Mikrotik Wifi Router on PT. Garindo Sakti Jaya - Gatot Budi; Regian Fajari Lubis (Intelmatics, 2022)
Garindo Sakti Jaya is a physiotherapy health provider, as a company founded in 2009 it has not escaped the use of Internet media in work activities Company. The use of Internet media is expected to support employee performance. The challenge that does not often encounter in the use of Internet media is one less stable and less balanced network, for maximum increase and no less evenly between the user. So for the development of PT. Garindo Sakti Jaya requires network traffic management with features help with service quality (QoS). These problems can be predicted by using the router's features and access points. This research methodology using Mikrotik wireless bandwidth management i.e. a mechanism that allows users to use wireless clients optimally. Steps can be made to be able to produce maximum security and bandwidth analysis and testing can be done on the performance management of bandwidth by how to use the Mikrotik wireless router and the access point is Mikrotik router and access the pool point links. There are some parameters made in this study, among other things: the troughput parameter, the parameters and the parameter delays, loss of packages. Based on research that has been done using Mikrotik router generating applications that can satisfy the share of bandwidth and a fairly good WiFi manager on the client side or end user.